Effects of sta. fresh wax coating on the ripening of fresh solo papaya (Carica papaya, L. va. kapohol) - Dela Cruz, Maireen Christine T. (1998.)
The effect of Sta. Fresh 320 wax coating on the change in peel color, weight loss, pH, % titrable acidity (%TA) and % total soluble solids (%TSS) during storage of Solo Kapoho papaya was investigated.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Wax coating; Papaya